Inequality in the Indian Growth Regime*. Issue 2 (August 2018) - Rodgers, Gerry
Researchers and policymakers have traditionally been more concerned with poverty than with inequality in India but this is now changing. The long-term trend in India was for economic inequality to decline until the 1980s, but it has since been rising, especially in urban areas, and between urban and rural areas. Wages have been rising and absolute poverty has been falling, but there has been a tendency for the gains from growth to be concentrated among the highest income groups. This applies not only to income and expenditure but also to wealth. These trends reflect the social and economic institutions that underpin the changing growth regime in India—the macroeconomic framework; wage labour relations; agrarian relations; the competition regime; type of integration in the international economy; and the role of the state. These institutions and their interactions give rise to particular patterns of growth and distribution, which change over time, and which need to be analysed in historical context. The article briefly reviews the impact of these factors on inequality over the period since Independence, and suggests that the forces driving the upward path of inequality remain strong.